دراسة وبائية عن نخر الأسنان عند اليافعين في الساحل السوري - سلمان, بسام (Latakia University Journal -Medical Sciences Series, 2019)
هدفت هذه الدراسة إلى تحديد نسبة انتشار وشدة النخر السني عند الأطفال في عمر (13 – 15) سنة في الساحل السوري، وإلى دراسة تأثير العوامل المختلفة المؤهبة لحدوث النخر السني عند هؤلاء الأطفال، وعلاقتها مع درجة شدة النخر. أجريت الدراسة على 884 طفلاً ذكراً وأنثى تتراوح أعمارهم ما بين (13-15) سنة, تم تقسيم الأطفال إلى أربع مجموعات بالاعتماد على درجة شدة النخر السني لديهم، جرى تحديد العوامل المؤهبة للنخر السني (نوع الرضاعة، الامراض التي أصيب بها الطفل في مرحلة تشكل وبزوغ الأسنان الدائمة، نوع الأطعمة، مستوى العناية بالصحة الفموية) أظهرت النتائج انتشار النخر السني عند هذه العينة بنسبة 47و88 %, متوسط مشعر شدة النخر DMFT عند كل طفل 83و2. وأظهرت هذه الدراسة أهم العوامل التي تؤثر على شدة النخر السني: حيث اعتبر عامل الرضاعة الاصطناعية واحداً من هذه العوامل التي تميز بشكل جوهري في كل مجموعات الدراسة, عامل الأمراض المختلفة وأهمها الأمراض الزكامية الحادة الفموية، حيث وجدت فروق جوهرية بين المجموعات في موضوع عدم التفريش، وعدم المضمضة بعد تناول الطعام. وهذه النتائج تعطينا أسساً واضحة من أجل تحديد أفضل السبل والإجراءات الوقائية عن طريق إزالة هذه العوامل السيئة التي أظهرتها الدراسة. This study aimed to show the rate of prevalence and the grade of the intensity of the dental caries of children between 13 and 15 years old in the Syrian coast and to study the effects or the different factors which irritate dental caries and their relation with the grade of the intensity of the dental caries This study depends on 884 children, male and female between 13 and 15 years old. We divided the children intoto four groups depending on the grade of the intensity of the dental caries. We defined the factors that fit the dental cnries: the kinds of sucking; the facctor of the variety of diseases in the period of immortelle teeth growing; the factor of the food kinds and the level of the mouth health care. Results show that the prevalence of the dental caries in these children is 88.47 %; and the index average intensity DMFT of each child is 2.83. The study shows the most important factors that cause the intensity of the dental caries: industrial sucking, variety of diseases like the intense frequent flu, the kinds of food. Basic health differences were found among these groups in cases when the children do not brush their teeth and gargle after Eating. These results give a clear indication of how to define the best ways of getting rid of these bad factors shown in the study.